A Randomised, Cross over Study Using a Mannequin Model to Evaluate the Effects on CPR Quality of Real-Time Audio-Visual Feedback Provided by a Smartphone Application. Issue 3 (May 2014) - Park, CS; Kang, IG; Heo, SJ; Chae, YS; Kim, HJ; Park, SS; Lee, MJ; Jeong, WJ
Objective: To evaluate the effect of real time feedback provided by smartphone application on cardiopulmonary resuscitation (CPR) performance. Methods: Participants were randomised in two groups based on whether chest compression with or without the assistance of the smartphone application. Both groups performed hands-only CPR on a mannequin for 4 minutes. Data on CPR performance of both groups was compared. To assess the reliability the feedback value, we compared the CPR data from Skillmeter and data from smartphone. A questionnaire survey to participants about the usefulness of the application was also evaluated. Results: Twenty-one subjects were recruited for the study. We found no significant difference in mean chest compression rate (103.3±5.0/min vs. 107.1±1.7/min; p=0.133) and depth between the two groups (47.3 [39.3, 56.2] mm vs. 45.8 [40.3, 49.9] mm; p=0.085). The proportion of adequate compression depth over the total compression was significantly higher in the group using the smartphone (38.1% vs. 22.2%; p=0.034). The CPR data displayed on smartphone application in mannequin's chest was not different from Skillmeter software. The majority of the participants considered the application easy to use, but holding the smartphone during CPR hampered compression. Conclusions: Real-time audio-visual feedback on CPR depth and rate using a smartphone application can help to maintain the adequate chest compression depth in prolonged CPR. A better method to hold the smartphone may maximise the feedback effect on CPR quality. (Hong Kong j.emerg.med. 2014;21:153-160)